1993
DOI: 10.1577/1548-8667(1993)005<0294:eodaes>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet and Environmental Salinity on the Growth, Mortality, and Tissue Structure of Juvenile Striped Bass

Abstract: Juvenile striped bass Morone saxatilis (approximately 60 d old) were fed either a commercial trout feed or an open-formula salmon feed for 16 weeks and reared in 24°C fresh water or saline water prepared from sodium chloride or synthetic sea salt. Fish that were fed salmon feed were larger, contained higher levels of body lipid, and had livers with uniform glycogen vacuolation. Fish that were fed trout feed were smaller, contained less body lipid, and had necrotic liver tissue. More than 95% of the fish fed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…: +1 334 844 3474; fax: +1 334 844 9208; email: jgrizzle@acesag.auburn.edu 15-18‰ salinity (highest tested), slower growth in lower salinities, and had the lowest growth rate in fresh water. For some juvenile striped bass Morone saxatilis (Walbaum), growth is enhanced by salinities from 3 to 10‰ (Lemm et al, 1993;Secor et al, 2000), but fish from other locations have similar growth rates in salinities from 0·5 to 15‰ (Secor et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…: +1 334 844 3474; fax: +1 334 844 9208; email: jgrizzle@acesag.auburn.edu 15-18‰ salinity (highest tested), slower growth in lower salinities, and had the lowest growth rate in fresh water. For some juvenile striped bass Morone saxatilis (Walbaum), growth is enhanced by salinities from 3 to 10‰ (Lemm et al, 1993;Secor et al, 2000), but fish from other locations have similar growth rates in salinities from 0·5 to 15‰ (Secor et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the higher FCR in hybrid striped bass was not related to poor digestibility of the trout diet. Lemm et al (1993) suggested that type and level of dietary essential fatty acids of trout diets do not reflect the requirements of hybrid striped bass which may also explain the present observed lower performance of hybrid striped bass fed the present trout diets. The better performance of hybrid striped bass fed with the pike perch diet was, however, somewhat unexpected because the pike perch diet showed the highest protein excess of all present diets (Table 1, 54% compared to the reported requirement of around 40% (Brown et al 1992;Nematipour et al 1992;Webster et al 2001)).…”
Section: Discussionmentioning
confidence: 76%
“…Previous observations stating that trout diets are nutritionally inadequate for hybrid striped bass date back to 1993 (Lemm et al 1993), in which nutritional knowledge even for highly commercial aquaculture species like trout was largely incomplete. It may have been expected that hybrid striped bass perform well on advanced 'modern' trout diets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations